Turabi’s Revolution: Islam and Power in Sudan By Abdelwahab El-Affendi. Turabi's Revolution: Islam and Power in Sudan. London: Grey Seal, 1991, 208pp. (American Journal of Islam and Society, 1992)
The establishment of a new political system and social order as a resultof a conscious Islamization effort is an important event in contemporary worldhistory. The Islamic revolution in Iran and the establishment of an Islamicrepublic in that country in 1979 was such a landmark event. A developmentwhich may have a similar significance for the 1990s is the emergence of a formalsocial and political Islamization effort in Sudan following the revolutionof 1989. In Sudan, the National Islamic Front led by Hasan lbrabi is workingwith the revolutionary regime of Omar Hassan al-Bashir in a major effort totransform Sudan on the basis of a more active adherence to Islamic ideals andstandards.The Iranian and Sudanese experiences have many differences but also someimportant similarities. One of these is that in both cases, important intellectualleaders, the Ayatollah Khomeini in Iran and Hasan Turabi in Sudan, hadbeen engaged in a long-term effort to define what a truly Islamic political systemand social order should be. As a result, the revolutions of 1979 and 1989 broughtto power groups possessing explicit conceptualizations regarding the nature ofthe systems to be implemented and leaders who were willing to work withgovernments to assist in this process of conscious Islamization.Hasan lbrabi has a long history of active involvement in Sudanese politics.By 1989 he had helped to create both an effective political organization, theSudanese Muslim Brotherhood, and an articulated ideology of sociopoliticalIslamization. The organization and the ideology provide the foundation for whatwas in many ways to become “Turabi’s revolution.”Abdelwahab El-Affendi, a journalist, political scientist, and diplomat, providesus with a description and analysis of this intellectual and political force.His substantial account of lhrabi’s revolution has the special benefits and difficultiesof being written by “an Islamist engaged in studying the very movementwithin which I grew up and the general aims of which I still vehementlysupport.” This book becomes, as a result, a case study of a number of verydifferent but important topics. There is the very nature and methodology ofthe author and the undertaking, as well as the issues raised by the content of ...